International Society of Paediatric Oncology (SIOP) Global Mapping Program: Analysis of healthcare centers in countries of the Latin American Society of Pediatric Oncology (SLAOP) - Gorostegui-Obanos, M (2024)
Background: The International Society of Paediatric Oncology Society Global Mapping Program aims to describe the local pediatric oncology capacities. Here, we report the data from Latin America. Methods: A 10-question survey was distributed among chairs of pediatric oncology services. Centers were classified according to patient volume into high- (HVC; 100 or more new cases per year), medium- (MVC; 31–99 cases), and low-volume centers (LVC; 30 cases or less), respectively. National referral centers (NRC) were identified. Results: Total 307 centers in 20 countries were identified (271 responded), and 264 responses were evaluable, accounting for 78% of the expected cases (21,359 cases per year). Seventy-seven percent of patients are treated in public centers, including additional support by civil society organizations. We found that 66% of the patients are treated in 70 centers of excellence, including 21 NRC. There was a median of one pediatric oncologist every 21 newly diagnosed patients (44 for NRC), and in 84% of the centers, nurses rotated to other services. A palliative care team was lacking in 25% of the centers. LVC with public funding have significantly lower probability of having a palliative care team or trained pediatric oncology surgeons. Psychosocial, pharmacy, and nutrition services were available in more than 93% of the centers. No radiotherapy facility was available on campus in nine of 21 NRC. Conclusions: Most children with cancer in Latin America are treated in public HVC. There is a scarcity of pediatric oncologists, specialized nurses and surgeons, and palliative care teams, especially in centers with public funding.